2020
DOI: 10.15640/jhrmls.v8n2a3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Motivation on Job Performance: A Review of Literature

Abstract: The purpose of this research is to identify the impact of employee motivation on employee performance. Employee performance is the key to success of any organization. Therefore organizations implement various motivation policies and use a number of motivation methods to motivate their employees aiming employee performance. But how far these motivation method contribute to the employee performance is a researchable question.. Findings of the review confirmed that. employee motivation is having a positive relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…Based on the test results, supervision is not significant for employee work productivity at PDAM Tirta Silau Piasa, Asahan Regency. This research does not support the results of research conducted by Hemakumara (2020) and Anisya et al (2021), which stated that motivation significantly affects work productivity. Furthermore, this research supports the results of research (Putra and Mujiati, 2022;Bashir et al, 2020;Engidaw, 2021), which stated that motivation is not always able to increase employee morale.…”
Section: The Influence Of Motivation On Work Productivitycontrasting
confidence: 99%
See 1 more Smart Citation
“…Based on the test results, supervision is not significant for employee work productivity at PDAM Tirta Silau Piasa, Asahan Regency. This research does not support the results of research conducted by Hemakumara (2020) and Anisya et al (2021), which stated that motivation significantly affects work productivity. Furthermore, this research supports the results of research (Putra and Mujiati, 2022;Bashir et al, 2020;Engidaw, 2021), which stated that motivation is not always able to increase employee morale.…”
Section: The Influence Of Motivation On Work Productivitycontrasting
confidence: 99%
“…Furthermore, motivation is a desire within a person that causes that person to take action, and of course, this will affect a person's performance (Riyanto et al, 2021). If a person's work motivation is good, then that person's performance will also be good, and vice versa (Hemakumara, 2020). Work motivation is considered to have a positive relationship between motivation and work productivity (Andreas, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Similar positive relationships were found for universities in Turkey (Aydın, 2012), Ghana (Kwapong et al ., 2015) and Malaysia (Ghaffari et al ., 2017). Moreover, the positive relationship between employee motivation and job performance was confirmed for different industries and different countries in Asia, Africa and Europe (Hemakumara, 2020; Diamantidis and Chatzoglou, 2019) with certain national differences in the level of influence of particular motivational factors.…”
Section: Introductionmentioning
confidence: 88%
“…According to (Afandi and Khamidi, 2018), motivation is a desire that arises from within a person or individual because he is inspired, encouraged, and compelled to carry out activities with sincerity, pleasure, and earnestness so that the results of the activities carried out get good and quality results (Mahmoud et al, 2020). Previous research from (Irvan and Heryanto, 2019), (Hemakumara, 2020), (Santoso and Riyanto, 2020), and (Blegur and Amalia, 2019) confirmed that motivation has a significant positive effect on nurse performance. Based on this description, the hypothesis is formulated as follows:…”
Section: Theoretical Reviewmentioning
confidence: 99%